2018
DOI: 10.1016/j.jchemneu.2017.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Berberine confers neuroprotection in coping with focal cerebral ischemia by targeting inflammatory cytokines

Abstract: HighlightsBerberine reduces brain edema and infarct volume through regulation of inflammatory responses in focal cerebral ischemia.Berberine increases the expression of anti-inflammatory cytokines after ischemic stroke.Berberine contributes to recovery of motor function after focal cerebral ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 42 publications
4
31
0
Order By: Relevance
“…In their research, BBR has no effect on Akt or ERK 1/2 phosphorylation but reduces TLR4/MyD88/NF‐κB signaling. Through regulation of proinflammatory cytokines and anti‐inflammatory cytokines, BBR appeared to cope with focal cerebral ischemia and scopolamine‐induced neuronal impairment to exert its neuroprotection function (B. Lee, Sur, Shim, Lee, & Hahm, ; Maleki, Aboutaleb, & Souri, ). In addition to reduction of proinflammatory cytokines (TNFα, IL‐1β, and IL‐6) expression, BBR down‐regulates LPS‐ or IFN‐γ‐induced iNOS, NO, and COX‐2 in BV‐2 microglia cells through AMP‐activated protein kinase (AMPK) activation, which monitors the AMP/ATP ratio (D. Y. Lu et al, ).…”
Section: Inflammationmentioning
confidence: 99%
“…In their research, BBR has no effect on Akt or ERK 1/2 phosphorylation but reduces TLR4/MyD88/NF‐κB signaling. Through regulation of proinflammatory cytokines and anti‐inflammatory cytokines, BBR appeared to cope with focal cerebral ischemia and scopolamine‐induced neuronal impairment to exert its neuroprotection function (B. Lee, Sur, Shim, Lee, & Hahm, ; Maleki, Aboutaleb, & Souri, ). In addition to reduction of proinflammatory cytokines (TNFα, IL‐1β, and IL‐6) expression, BBR down‐regulates LPS‐ or IFN‐γ‐induced iNOS, NO, and COX‐2 in BV‐2 microglia cells through AMP‐activated protein kinase (AMPK) activation, which monitors the AMP/ATP ratio (D. Y. Lu et al, ).…”
Section: Inflammationmentioning
confidence: 99%
“…In addition, it has been reported that a severer aspect of neuronal loss/death in the hippocampus is shown following 15 min of TFI than that in 5 min TFI in gerbils [ 2 ]. Furthermore, a rat model of focal brain ischemia induced by MCAO for over 1 h develops infarct lesion (necrotic tissue) which is easily visualized by 2, 3, 5-triphenyltetrazolium chloride (TTC) assay, but infarction does not occur in the brain induced by TFI for 5–15 min in gerbils when the TTC assay is applied, in which selective neuronal death only occurs [ 1 , 15 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that pro-inflammatory cytokines exacerbate and advance deleterious inflammatory processes, but anti-inflammatory cytokines suppress the expressions of pro-inflammatory cytokines and bring advantageous inflammatory processes in ischemic brains [ 10 , 52 ]. In this regard, many studies have reported that increases in anti-inflammatory cytokine expressions present neuroprotective effects following ischemia-reperfusion injuries [ 10 , 32 , 50 , 53 ]. In our current study, pro-inflammatory cytokines (TNF-α and IL-2) were increased in the CA1 pyramidal cells following TFI; however, pretreated 30 mg/kg CGA inhibited these increases and elevated the expression levels of anti-inflammatory cytokines (IL-4 and IL-13).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that berberine when administered at nanomolar concentration it promotes cell survival and reduces oxidative stress by downregulating various factors such as cytochrome c, Bax and caspase. In the case of ischemic stroke, it has been observed that administration of berberine can protect by inhibiting potassium currents [ 60 ].…”
Section: Overview Of Phytochemicalsmentioning
confidence: 99%